KEEFEKTIFAN KONSELING KELOMPOK MENGGUNAKAN PENDEKATAN CBT DALAM MENGURANGI KECEMASAN SOSIAL ANAK BINAAN LPKA - Winarti, Rahayu; Wicaksono, Luhur; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This article examines the effectiveness of group counseling using Cognitive Behavioral Therapy (CBT) approach in reducing social anxiety among children at LPKA Class II Sungai Raya. The purpose of this study was to determine the effectiveness of group counseling using CBT approach in reducing social anxiety among children at LPKA Class II Sungai Raya. The research method used was experimental with a pre-experimental design, specifically the Pre-test-Post-test One Group Design. The sample was taken using non-probability sampling technique with purposive sampling type. A total of 8 children with high social anxiety levels were selected from a population of 30 children with high social anxiety levels. Based on the calculation, the average pre-test score was 154.125, and the post-test score was 86.875. Furthermore, the Paired Sample T-test yielded a T-value of 12.052 with a Sig. (2-tailed) value of 0.000 < 0.05, and an Effect Size of 7.50 (high), which means Ha is accepted and H0 is rejected. This indicates that there is a significant difference in social anxiety levels among children before and after receiving group counseling using CBT approach. Therefore, it can be concluded that group counseling using Cognitive Behavioral Therapy (CBT) approach is effective in reducing social anxiety among children at LPKA Class II Sungai Raya.